Analisis Dampak Menonton Serial Kartu Upin dan Ipin Terhadap Perkembangan Moral Agama Anak Usia 5-6 Tahun - Fatimah Depi Susanty Harahap; Nur Atimah Nasution (TANJAK, 2022)
This research aimed at knowing the impact of watching Upin and Ipin cartoon series to religious moral development of 5-6 years old children. This research was motivated to know the positive and negative impacts of watching Upin and Ipin cartoon series to religious moral development of 5-6 years old children. Religious moral development was the children ability in behaving. Islam taught about the positive values that were useful in social life. This caused need religious moral development for 5-6 years old children. It was library research. Primary and secondary data were used in this research. Documentation technique was used for collecting the data. Descriptive method was used for analyzing the data. The findings of this research showed that there were positive and negative impacts of watching Upin and Ipin cartoon series to religious moral development of 5-6 years old children. The positive impacts: children were more aware of religious morals themselves, in the family and in society or the environment. The negative impacts: children imitated the negative morals of the Upin and Ipin cartoon series.